Desenvolvimento de protótipo de módulo didático digital baseado na tecnologia FPGA - Fermiani, Rodrigo Maraschin (2015)
This work describes the programming and building of a prototype, will serve as a teaching application for the Digital Systems Laboratory of UTFPR. The work aims to study and use the knowledge in the embedded systems area, specifically FPGA’s and hardware description language - VHDL, to creation of a prototype of a digital didactic module. Were identified hardware requirements and defined the FPGA model (EP2C5T144). Study and development of digital logic circuits routines in VHDL. Building, configuration and prototype testing. Defined the model of FPGA, Altera’s manufacturer, it was necessary to study the Quartus II software. This software communicates the codes described to the FPGA. Six main projects were developed, as combinational logic circuits (adders, encoders) and sequential (counters) and the using of peripheral circuits. The codes developed were tested in laboratory and the results were consistent with the simulated ones. In addition, it elaborated additional supporting material, a tutorial for using the Quartus II and a material with the logical circuits and VHDL codes of the projects builded, both available in the appendices.